"This isn't my real writing": The fate of children's agency in too-tight curricula. Issue 2 (2nd April 2020) - Dyson, Anne Haas
ABSTRACT: In this article, I adopt a practice theory consideration of student agency, that is, I consider students' power to act on their interests and intentions, on their own inclinations; this will-to-act-on-the-world is central to becoming an active, adaptive participant across the life span. As practice theorist Shery Ortner has explained, none of us have unencumbered agency; we are all constrained and empowered by the institutional structures within which we live. Influenced by practice theory, I draw on ethnographic studies to examine the dynamics through which increasingly structured classrooms for young school children may dampen child agency or push it underground or out-of-school, thereby pushing out as well important dimensions of children's intellectual energy. I conclude with a consideration of what makes young children's composing, or any constructive and creative act, willful and intentional, that is, "real."